1989
DOI: 10.4141/cjss89-006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Constituents in Manure on Denitrification in Soil

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 29 publications
6
62
0
Order By: Relevance
“…The denitrification rates were significantly higher than previous measurements , possibly due to higher NO x À concentrations, which have been linked to denitrification rate (Bartoli et al, 2012;Song et al, 2014;Lan et al, 2015). Propionate was also significantly correlated with denitrification (Supplementary Material Table S1) as demonstrated previously (Paul and Beauchamp, 1989;Hallin and Pell, 1998;Chen et al, 2015). Our results demonstrated that denitrification contributed to 90% of the N loss in both rhizosphere and bulk soils, indicating that denitrification is the main pathway of N loss in paddy soils over the period of rice growth, even when the rhizosphere provides a more favorable habitat for anammox bacteria.…”
Section: Discussionsupporting
confidence: 63%
“…The denitrification rates were significantly higher than previous measurements , possibly due to higher NO x À concentrations, which have been linked to denitrification rate (Bartoli et al, 2012;Song et al, 2014;Lan et al, 2015). Propionate was also significantly correlated with denitrification (Supplementary Material Table S1) as demonstrated previously (Paul and Beauchamp, 1989;Hallin and Pell, 1998;Chen et al, 2015). Our results demonstrated that denitrification contributed to 90% of the N loss in both rhizosphere and bulk soils, indicating that denitrification is the main pathway of N loss in paddy soils over the period of rice growth, even when the rhizosphere provides a more favorable habitat for anammox bacteria.…”
Section: Discussionsupporting
confidence: 63%
“…Manure application probably resulted in denitrification of soil NO 3 -already present in the soil. Paul and Beauchamp (1989) showed that denitrification of soil NO 3 -occurred within hours of manure application due to oxidation of short-chain fatty acids present in manure which served both to provide electron donors for the denitrifying bacteria and to increase the oxygen demand in the soil. In the present experiments, denitrification was not measured during the first week following manure application, therefore denitrification losses occurring shortly after manure application were not included in denitrification loss estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that denitrification losses are higher in manured soils than in non-manured soils (Burford et al 1976;Rolston et al 1984;Christensen 1985;Paul and Beauchamp 1989). Thompson (1989) and Goulding and Webster (1989) measured increased denitrification losses in the fall or winter from fall-applied manure.…”
mentioning
confidence: 99%
“…Reinertsen et al (1984) observed that soil microbial biomass C and the decomposition of straw were largely dependent on the quantity of soluble C at early stages of decomposition. Soluble C has been reported to be a good indicator of the availability of C to sustain denitrifi-cation activity (Burford and Bremner 1975;Davidson et al 1987;Paul and Beauchamp 1989). However, other studies have found that not all of the soluble C is readily decomposable (Horwath and Elliott 1996) and that the recalcitration fraction increases with incubation time (Cook and Allan 1992).…”
mentioning
confidence: 89%